THE EFFECTS OF STUDENT’S PERCEPTION ON USING AUDIO VISUAL MEDIA AND INDEPENDENT LEARNING TOWARDS STUDENT’S READING SKILL (Survey at State Senior High School in East Jakarta) - Rina Husnaini Febriyanti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2013)
The aim of this research is to know the effects of student’s perception on using audio visual media and independent learning altogether towards student’s reading skill. And, to know the effect of student’s perception on using audio visual media towards student’s reading skill, next, to know the effect of independent learning towards reading skill. The research method which is used is survey. The amount of sample is 60 students who are chosen randomly (cluster random sampling) out of 3 schools in East Jakarta (SMA Negeri 88, 99, and 51 Jakarta) grade X in academic year 2012/2013. The data collection is implemented by using the technique of spreading 2 kinds of questionnaires and 1 kind of multiple choice test. The scale which is used for the questionnaires are Likert scale, the validity is calculated by using coefficient correlation of Pearson- Product Moment, and reliability is formulated by using Cronbach Alpha Method the result is 0,813 it is for student’s perception on using audio visual media and it is 0,555 for independent learning. For the test, the validity of student’s reading skill is calculated by using Point Biserial, and the reliability is formulated using Kuder Richardson-20 the result is 0, 8721.Key Word: Student’s Perception On Using Audio Visual Media, Independent Learning, Student’s Reading Skill